Influence of social change regarding the issue of wives’ salary spent by husbands: An analysis - Siti Fatimah, Salleh; Wan Mohd Khairul Firdaus, Wan Khairuldin; Zurita, Mohd. Yusoff; Tengku Fatimah Muliana, Tengku Muda; Siti Khatijah, Ismail (2016)
Social change is one instrument that supposed to be taken into consideration in the current Islamic jurisprudence settling. Working women do give implications towards the social change in society as well as the rectification of syarie law that is emerged due to their participation in certain industries. The objectives of this article are to analyze the elements of social changes that occur attributable to the women involvement in labor and the Islamic law of the expenditure of wives’ salary by husbands. The methodology of this paperwork is through the literature review on the analysis of data from primary and secondary sources in the social sciences and syarie field as well as through interviews. The outcome of the study found out that the implication of social change and the involvement of women in labor do give certain Islamic law implication on it including the law of women who do labor, their living, and husbands who spend their wives’ money in daily basis.